Strategic Marketing: The Key to Success in Maximizing Event Management - Adi Suryo Ramadhan; Agus Wibowo (Jurnal Publikasi Ilmu Manajemen, 2022)
Organizations have an interest in holding various activities supporting the enterprise's image branding and product marketing. Events as media or communication activities certainly also require planning and marketing strategies so that the events carried out are successful. The purpose of this study is to examine the role of strategic marketing in achieving success in event management. This research involved the contribution of 206 respondents who were obtained through the SurveyMonkey questionnaire which was distributed via email, WhatsApp and Instagram. Methods of data analysis using the mean and linear regression processed with SPSS. This research focuses on the study of marketing strategies which include price, promotion and product differentiation which effect on the success of the event menegement. The findings show that pricing, promotion and product differentiation strategies have a significant influence on the success of the event. The recommendations given in this study are that companies need to devise and define a marketing strategy which includes price, promotion, product and distribution. By establishing a clear marketing strategy, the company's excellence can be increased and achieve better performance.